(untitled) - Bourne, Lyle Eugene (New York, 1979)
Contents: The nature of psychology; biological foundations of behavior; Sensation and perception; basic principles of learning; human learning and memory; motivation and emotion; social psychology; psychopathology; psychotherapy.
Keywords: Psychology